Tanggung Jawab Sosial, Ekonomi, dan Ekologis dalam Perspektif Teologi Pastoral: Refleksi atas Bencana di Indonesia dalam Terang Gaudium et Spes 63–72 - Rosalia Enny Astuti; Sutami, Florensius; Wyatno, Anthony Kuniawan; Anang, Noverin Andrea; Simanjuntak, Helmina; Hartanto, Sukiahwati; Pailing, Yulius Roge (JURNAL KADESI, 2026)
Indonesia is a disaster-prone region where calamities are frequently exacerbated by the spiritual crisis of modern humanity, manifested as individualism and a dominant technocratic paradigm,This article explores social, economic, and ecological responsibilities in light of the Pastoral Constitution Gaudium et Spes (GS) articles 63–72 and the encyclical Laudato Si’ (LS) as a response to the reality of disasters in Indonesia,The research employs a qualitative approach using a descriptive-analytical method based on library research Findings indicate that GS 63–72 positions human dignity at the center of economic life, where the principle of the "universal destination of goods" (GS 69) serves as an ethical foundation for the just distribution of resources during disaster emergencies. Furthermore, the concept of integral ecology expands socio-economic responsibility into an ecological dimension, highlighting the intrinsic link between the "cry of the earth" and the "cry of the poor"This theological analysis advocates for a transformation toward a holistic pastoral care model that integrates the needs of individuals, society, and the environment. The study concludes that ecological conversion and the implementation of a preventative, contextual "ecological diaconia," enriched by local wisdom, are essential for caring for our common home.